Case Report: CMV Infection and Same Mechanism-Originated Intestinal Inflammation Compatible With Bowel/Crohn's Disease Is Suggested in ATP4A Mutated-Driven Gastric Neuroendocrine Tumors - Calvete, Oriol; Reyes, José; Benítez, Javier (Frontiers in Medicine, 2021)
Mutations in the ATP4A proton pump prevent gastric acidification and explain the chronic autoimmune gastritis scenario that conducts the gastric neuroendocrine tumour (gNET) formation. Here, we wanted to investigate the co-occurrence cytomegalovirus (CMV) infection and intestinal inflammation that presented all members of a family affected with gNET and carrying an ATP4A mutation. Intestinal inflammation persisted after CMV eradication and anaemia treatment. The inflammation was compatible with a ileitis/Crohn's disease and was originated by the same autoimmune mechanism described in the tumorigenesis of gNETS. The same secondary disease but no the CMV infection was observed in all members affected with gNET and carrying the ATP4A mutation. Our results suggest that the ATP4A malfunction not only explained gNETs but also the co-occurring disease and opportunistic infections, which allowed to link autoimmune pathologies and gNETs in a unique mechanism. Our results open a new window to better understand not only gastric neoplasms formation but the co-occurring autoimmune disorders and the inflammatory mechanism that compose a premalignant scenario for other tumour formation. Our findings are important since contribute to describe the genetic landscape of the Inflammatory Bowel/Crohn’s disease and alert clinicians to monitor patients with gastric neoplasms mediated by achlorhydria mechanisms for concomitant secondary pathologies.